Penguatan Peran Keluarga dalam Pencegahan Stunting melalui Sosialisasi Makan Bergizi Berbasis Pangan Lokal di Kabupaten Rote Ndao - Apris Adu; Mas'Amah (Yayasan Sumber Daya Manusia Cerdas, 2025)
Stunting remains a major nutritional problem in Indonesia, particularly in East Nusa Tenggara Province, including Rote Ndao Regency, where prevalence rates remain above the World Health Organization threshold. Stunting prevention requires comprehensive strategies that extend beyond medical interventions by strengthening the role of families as primary caregivers. This community service activity aimed to enhance family capacity in stunting prevention through balanced nutrition socialization using a family empowerment approach. The program was conducted in Lobalain District, Rote Ndao Regency, in July 2025, involving 25 mothers with school-aged children and toddlers. The intervention consisted of nutrition education, interactive discussions, and practical simulations of preparing nutritious meals using local food resources. Program evaluation was carried out through pre-test and post-test assessments to measure knowledge improvement and observation of participants’ food processing skills. The results demonstrated a significant increase in maternal nutrition knowledge, with mean scores rising from 60.0 to 78.2 (p < 0.05). Participants also showed improved skills in processing local foods into nutritious products. These findings indicate that a family empowerment-based approach is effective in strengthening maternal knowledge and skills, contributing to sustainable stunting prevention efforts at the household level.